MODEL GEORGE EDWARD III - Setyawan, Dody; Priantono, Agus; Firdausi, Firman (Universitas Panca Marga, 2021)
Indonesia is a country with highest number of smokers in the world with high mortality. The dangers of smoking not only threaten active smokers but also passive smokers. Policies are necessary to protect and reduce its adverse effects of smoking. At the regional level in 2018, the Malang City Government passed a Regional Regulation that regulates Non-Smoking Areas (KTR). The realization and efforts to implement this regional regulation are the objectives of the research. Qualitative method is used, the focus of research is to determine the four indicators popularized by George Edward III. Determination of informants determined by purposive sampling. Primary data was obtained through in-depth interviews, observations, and related document studies. The data analysis technique uses an interactive model according to Miles, Huberman & Saldana. Regional Regulation Number 2 of 2018 in Malang City in its implementation has not run effectively, yet the harmonization of this Regional Regulation with the Mayor's Regulation is the main obstacle. The development of smoking area facilities has not been maximized and the socialization of this regional regulation is still limited to policy implementers.